2017
DOI: 10.1103/physrevb.95.134420
|View full text |Cite
|
Sign up to set email alerts
|

Slow spin tunneling in the paramagnetic phase of the pyrochlore Nd2Sn2O7

Abstract: The insulating pyrochlore compound Nd2Sn2O7 has been shown to undergo a second order magnetic phase transition at Tc ≈ 0.91 K to a noncoplanar all-in-all-out magnetic structure of the Nd 3+ magnetic moments. An anomalously slow paramagnetic spin dynamics has been evidenced from neutron backscattering and muon spin relaxation (µSR). In the case of µSR this has been revealed through the strong effect of a 50 mT longitudinal field on the spin-lattice relaxation rate. Here, motivated by a recent successful work pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…For the DO doublet, the wave function of each state in the doublet is a linear superposition of |J z = 3n/2 where n is an odd integer. The DO doublet was found to be applicable to Nd 3+ in Nd-based pyrochlores [37][38][39][40][41][42][43][44], Sm 3+ in Sm 2 Ti 2 O 7 [45,46], Ce 3+ in Ce 2 Sn 2 O 7 [34,47,48], and Ce 2 Zr 2 O 7 [49][50][51] and Er 3+ in the spinels [52,53]. DO doublets can broadly exist in magnets with a D 3d point-group symmetry, other lattices such as honeycomb magnets could support the DO doublet [54].…”
Section: Nondegenerate Dipole-multipole Doublet Of Tm 3+ Ionmentioning
confidence: 98%
“…For the DO doublet, the wave function of each state in the doublet is a linear superposition of |J z = 3n/2 where n is an odd integer. The DO doublet was found to be applicable to Nd 3+ in Nd-based pyrochlores [37][38][39][40][41][42][43][44], Sm 3+ in Sm 2 Ti 2 O 7 [45,46], Ce 3+ in Ce 2 Sn 2 O 7 [34,47,48], and Ce 2 Zr 2 O 7 [49][50][51] and Er 3+ in the spinels [52,53]. DO doublets can broadly exist in magnets with a D 3d point-group symmetry, other lattices such as honeycomb magnets could support the DO doublet [54].…”
Section: Nondegenerate Dipole-multipole Doublet Of Tm 3+ Ionmentioning
confidence: 98%
“…It has been recently shown that careful analyses of µSR spectra recorded in correlated paramagnetic regimes can yield useful information [31,42]. The spectra for the two compounds of interest here are best described as the weighted sum of two dynamical Kubo-Toyabe functions; see Fig.…”
Section: µSr Resultsmentioning
confidence: 99%
“…"Dipolar-octupolar" (DO) pyrochlores R 2 M 2 O 7 (R=Ce, Sm, Nd; M=Zr, Hf, Ti, Sn, Pb) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] constitute an opportunity in this context, with their low-energy physics being described by a simple XY Z Hamiltonian [45,46]. Out of this family, Ce 2 Sn 2 O 7 [27,28] and Ce 2 Zr 2 O 7 [29,30] have been highlighted recently as showing evidence of QSL physics.…”
Section: Introductionmentioning
confidence: 99%